Computerized Databases for Emergency Care: What Impact on Patient Care? - Pugh, G. E.; Tan, J. K. H. (Methods of Information in Medicine, 1994)
A field-based evaluation is conducted of a Clinical Computerized Information System (CCIS™). Following training, the use of the CCIS™ database, word processing and other programs by thirteen full-time practicing emergency physicians in two urban emergency departments of a University-associated teaching hospital was studied over a one-year period. A tracking program automatically logged frequency and duration of use by the physicians, and user satisfaction was assessed by a reliable and validated questionnaire instrument. Based on utilization data and verbal reports of these physicians, CCIS™ database searching was not only found to be easy-to-leam but was readily accessible during emergency shifts. Individual physicians were found to perform an average of 3.5 searches per month lasting a mean search time of 8 min. Positive notes about the CCIS™ system included ease-of-use, accuracy of data, accessibility of system, and value of output while negative perceptions included a lack of integration with other systems, a lack of system completeness, and a high subscription cost. It was suggested that a less costly telephone link to a high-volume Centre would be desirable in actual implementation of the system.
Keywords: Clinical Information Systems; Databases; User Satisfaction; Software Evaluation; Technology Management